Reconsidering Asian American Student Development. Issue 160 (20th December 2017) - Kodama, Corinne M.; Maramba, Dina C.
Abstract: This chapter addresses the applicability of student development theories in light of empirical research on Asian American college students through a twofold approach: (a) revisiting the relevance of Kodama, McEwen, Liang, and Lee's (2001, 2002) theoretical work on Asian American student development; and (b) using Jones' and Stewart's (2016) framework to complicate thinking on new paradigms for understanding and advancing student development theory and research.